2022
DOI: 10.3389/fphar.2022.798349
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lisinopril Raises Tissue Levels of ACE2, the SARS-CoV-2 Receptor, in Healthy Male and Female Mice

Abstract: Angiotensin-converting enzyme 2 (ACE2) is the established cellular receptor for SARS-CoV-2. However, it is unclear whether ACE1 inhibitors (e.g., lisinopril) or angiotensin receptor blockers (e.g., losartan) alter tissue ACE2 expression. This study sought to determine whether lisinopril or losartan, as monotherapies or in combination, changes tissue levels of ACE2 in healthy male and female mice. Mice received lisinopril (10 mg/kg/day), losartan (10 mg/kg/day), or both for 21 days via drinking water. A control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In contrast, the combination of lisinopril with losartan prevented the lisinopril-induced increase in tissue ACE2 levels. And so, the expression of ACE2 is different in different tissue [31].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the combination of lisinopril with losartan prevented the lisinopril-induced increase in tissue ACE2 levels. And so, the expression of ACE2 is different in different tissue [31].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ACE2 expression in patients with hypertension and diabetes is high due to the long-term medication of ACE inhibitors. A previous study on mice showed that ACE blockers increase the expression of ACE2 in the small intestine, lung, kidney, and brain; consequently, this may increase the risk of infection or reinfection, resulting in high virus titters [ 32 ]. In our study population, participants with one or more comorbidity diseases may be at increased risk of developing post-COVID-19 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent preprint article reported that the ACE inhibitor Lisinopril can raise the ACE2 expression landscape in the lungs, small intestine, kidney and brain of healthy mice, an effect that persists to at least 21 days post-termination of treatment (Brooks et al, 2022). Captopril, which also acts as an ACE inhibitor, appears to improve lung pathology and reduce inflammation during SARS-CoV2 infection in an angiotensin II-induced hypertensive and hACE2-expressing mouse model, without any detectable effect on viral load (Gao et al, 2021).…”
Section: Hypertensionmentioning
confidence: 99%